The fate of heavy metals in the co-processing of solid waste in converter steelmaking. (1st June 2022) - Long, Hua; Huang, Xinyu; Liu, Meijia; Cui, Changhao; Li, Li; Liao, Yang; Yan, Dahai
Abstract: The improper disposal of large amounts of solid waste (SW) has led to serious ecological and environmental problems, especially heavy metal (HM) pollution. Converter steelmaking has the potential to co-process SW, but the distribution of heavy metals (HMs) during converter steelmaking is unclear. In this study, the effects of smelting temperature and slag alkalinity on the distribution of typical HMs in the SW of steel samples, steel slag, and the gas phase were investigated in a specially-made induction furnace. The results showed that upon increasing the smelting temperature, As (As2 S3 ) was mainly distributed in the steel sample, and the HM-containing compounds Cr2 O3, CrCl3, ZnCl2, ZnS, ZnO, PbCl2, PbS, and PbO were mainly distributed in the gas phase. Upon increasing the alkalinity within a certain range, the distribution of HMs in steel samples and steel slag increased gradually, while their distribution in the gas phase decreased. Thermodynamic calculations, Eh-pH diagrams, XRD patterns, and XPS spectra indicated that impurity elements in the hot metal and the CaO content affected the chemical reactions by which HM-containing compounds in the steel sample formed elemental HMs and those in steel slag existed as oxides; therefore, it is necessary to choose a suitable temperature and alkalinity for slag when disposing of different types of SW. Graphical abstract: Image 1 Highlights: Typical heavy metal distribution characteristics in converter are verified by induction furnace simulation and theoretical calculation. Typical heavy metal distribution mechanism in three phases affected by temperature and alkalinity is revealed. Heavy metal-containing chloride, sulfide and oxide are existed in steel slag as oxide. Heavy metal-containing compounds are reduced to heavy metal element into molten steel.